Strengthening the Profile Pancasila Students and the Profile Rahmatan Lil Alamin Stdents in the Implementation Merdeka Curriculum at Madrasah Ibtidaiyyah - Anisah, Ani Siti; Masripah, Masripah; Saifullah, Iman (Al-Aulad: Journal of Islamic Primary Education, 2024)
The P5P2RA project is part of the implementation of the Merdeka Curriculum in Madrasas. Through the P5P2RA Project, we build students' character so that they have attitudes that are by the values of Pancasila and Rahmatan Lil'alamin. This research aims to describe the process of strengthening student profiles at the Madrasah Ibtidaiyyah level with research subjects involving the components involved in the Implementation of the Independent Curriculum at MIN 4 Garut with students in class I and class IV as the objects. The research method used is descriptive qualitative, using interviews, observation, and documentation as data collection tools. Data analysis uses triangulation techniques, namely data reduction, data display, and conclusion drawing/verification. The research results show that through the P5P2RA project activities, students' attitudes of independence, creativity, and tathawur wa ibtikar experience development. Through observation activities, teachers can diagnose children's attitudes before project activities through diagnostic assessments, and observe through summative assessments at the end of project activities. The development of students' attitudes can be seen from the results of summative assessment observations, this occurs through the learning process when carrying out contextual project activities. Through P5P2RA activities, students learn to observe their peers so that students gain knowledge, understand rules, increase skills, and have strategies and beliefs in developing attitudes.